2020
DOI: 10.4093/dmj.2019.0151
|View full text |Cite
|
Sign up to set email alerts
|

Differential Profile of Plasma Circular RNAs in Type 1 Diabetes Mellitus

Abstract: Background: No currently available biomarkers or treatment regimens fully meet therapeutic needs of type 1 diabetes mellitus (T1DM). Circular RNA (circRNA) is a recently identified class of stable noncoding RNA that have been documented as potential biomarkers for various diseases. Our objective was to identify and analyze plasma circRNAs altered in T1DM. Methods: We used microarray to screen differentially expressed plasma circRNAs in patients with new onset T1DM (n=3) and age-/gender-matched healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Another study detected 8,214 circRNAs in human plasma by microarray analysis of the samples of three subjects with new-onset T1DM and identified 61 upregulated and 7 downregulated circRNAs. Notably, the results of gene analysis revealed that these differentially expressed circRNAs participate in inflammation and the pathogenesis of T1DM ( 9 ), supporting the future applications of circRNAs as novel biomarkers of T1DM. Additionally, hsa_circ_0072697 is significantly downregulated in patients with T1DM ( 40 ).…”
Section: Role Of Circrnas In T1dmmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study detected 8,214 circRNAs in human plasma by microarray analysis of the samples of three subjects with new-onset T1DM and identified 61 upregulated and 7 downregulated circRNAs. Notably, the results of gene analysis revealed that these differentially expressed circRNAs participate in inflammation and the pathogenesis of T1DM ( 9 ), supporting the future applications of circRNAs as novel biomarkers of T1DM. Additionally, hsa_circ_0072697 is significantly downregulated in patients with T1DM ( 40 ).…”
Section: Role Of Circrnas In T1dmmentioning
confidence: 87%
“…CircRNAs can serve as the sponges for specific miRNAs to further regulate the expression levels of the target genes. Advancement of RNA sequencing technology and bioinformatics-based prediction resulted in identification of an increasing number of circRNAs and their biological functions (6,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs are widely distributed in different tissues, blood, and urine as well as saliva where their extractions are easy to conduct [ 22 ]. Because of their tissue and cell specificity, high-throughput sequencing of circRNAs using specific tissues and especially certain cells is the basis of accurate research, and circRNAs in body fluids are potential diagnostic markers [ 30 , 31 ]. For instance, the biomarker potential of circRNAs can be increased if they were found in exosomes, as has been evidenced in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Among them, the long non-coding RNA (lncRNA) is a kind of linear non-coding RNA with a length of more than 200 nucleotides, 21 and circular RNA (circRNA) is a kind of endogenous non-coding RNA with a closed-loop structure. 22 Previous studies have shown the vital roles of various lncRNAs and circRNAs in T1DM. lncRNA Lnc13 is up-regulated in β-cells and contributes to the pathogenesis of T1DM by increasing pancreatic β-cell inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al and Luo et al identified the circRNA-miRNA-mRNA network in T1DM via bioinformatic analysis. 22 , 33 Shi et al reported the lncRNA-miRNA-mRNA regulatory networks in T1DM. 34 Thus, further studies aimed at clarifying ceRNA-based molecular mechanisms in T1DM are needed to provide potential opportunities for better understanding the pathogenesis and treatment of T1DM.…”
Section: Introductionmentioning
confidence: 99%